Radiolytic degradation of ornidazole in aqueous solutions by electron beam irradiation: Implications to parameters, kinetics, toxicity and cost evaluation. Issue 5 (October 2020) - Changotra, Rahil; Guin, Jhimli Paul; Khader, Shaik Abdul; Dhir, Amit
Graphical abstract: Highlights: Electron beam induced degradation of ornidazole was explored. Oxidative pathway dominates the radiolytic degradation of ornidazole. Scavenging rates of HO, e a q - and H from different water matrices were calculated. Degradation mechanisms of ornidazole were proposed with identification of eight major products. Cytotoxicity evaluation revealed that ornidazole and its degraded products did not acquire any toxicity. Abstract: The study is aimed to assess the effectiveness of electron beam (EB) technology to degrade the antibiotic ornidazole (ORN) in aqueous solution. The influence of several factors viz. initial ORN concentrations, dose, pH of solution, and addition of N O 2 −, N O 3 −, isopropanol, H2 O2, thiourea, and different water mediums were evaluated on the ORN degradation. The degradation of ORN was followed by pseudo first-order reaction kinetics with rate constant value of 2.01, 1.17, 0.87 and 0.70 kGy −1 for the initial concentrations of 25, 50, 75, and 100 mg L −1 with their corresponding (G-(ORN) ) values of 0.93, 1.60, 1.97, and 2.12 μmol J −1, respectively. The presence of N O 2 −, thiourea and isopropanol revealed reduction in the k -value, whereas, addition of N O 3 − anion had not substantially effected the degradation of ORN. Presence of H2 O2 exhibits significant effect on the mineralization efficiency of ORN rather than degradation extent. The efficacy of EB irradiation to degrade ORN decreased in wastewater in comparison to surface, ground and ultrapure water. Based on the LC-QTOF-MS study, it could be ascribed that degradation of ORN was primarily due to the oxidative species HO radical and direct cleavage of ORN compound. Tentative pathways for EB-induced radiolytic degradation of ORN were proposed. Cytotoxicity assessment and overall cost of electrical energy consumed for the degradation of ORN was also evaluated.